The Level of Gratification in Using a Second Account Instagram for Self Disclosure - Aliyani, Nafi Rahima; Purworini, Dian (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study aims to find out how much the level of gratification in using a second account Instagram for self-disclosure. Methodology: This study used descriptive quantitative methods. The population used in this study is late adolescents aged 18-22 years old at the Faculty of Communication and Informatics UMS, who have and actively use a second account Instagram. The sample is determined by purposive sampling, and the data analysis was carried out with a paired sample t-test. Results: The results of this study show that there is gratification in the use of a second account Instagram for self-disclosure, this is based on the results of the comparison of the total mean value of gratification sought (GS) of 66.22, which has lower results than the total mean value of gratification obtained (GO) of 67.39. So, the social media second account Instagram can provide a sense of gratification to the audiences. There is a significant difference between GS and GO in this study, which is the value from the Sig (2-tailed) result is 0.002<0.05. So, there is a significant difference between the variables. The hypothesis result of this study is H0 rejected and Ha accepted. Applications/Originality/Value: This study seeks to describe the level of gratification in using a second account Instagram for self-disclosure by using 4 indicator motives for media use, namely information, personal identity, integration and social interaction, and entertainment. The differences between this study with the other study lie in the population, research object, literature, and research results.